Additive Value of Biomarkers and Echocardiography to Stratify the Risk of Death in Heart Failure Patients with Reduced Ejection Fraction. (2nd May 2019) - Falletta, Calogero; Clemenza, Francesco; Klersy, Catherine; Agnese, Valentina; Bellavia, Diego; Di Gesaro, Gabriele; Minà, Chiara; Romano, Giuseppe; Temporelli, Pier Luigi; Dini, Frank Lloyd; Rossi, Andrea; Raineri, Claudia; et al.
Abstract : Background . Risk stratification is a crucial issue in heart failure. Clinicians seek useful tools to tailor therapies according to patient risk. Methods . A prospective, observational, multicenter study on stable chronic heart failure outpatients with reduced left ventricular ejection fraction (HFrEF). Baseline demographics, blood, natriuretic peptides (NPs), high-sensitivity troponin I (hsTnI), and echocardiographic data, including the ratio between tricuspid annular plane excursion and systolic pulmonary artery pressure (TAPSE/PASP), were collected. Association with death for any cause was analyzed. Results . Four hundred thirty-one (431) consecutive patients were enrolled in the study. Fifty deaths occurred over a median follow-up of 32 months. On the multivariable Cox model analysis, TAPSE/PASP ratio, number of biomarkers above the threshold values, and gender were independent predictors of death. Both the TAPSE/PASP ratio ≥0.36 and TAPSE/PASP unavailable groups had a three-fold decrease in risk of death in comparison to the TAPSE/PASP ratio <0.36 group. The risk of death increased linearly by 1.6 for each additional positive biomarker and by almost two for women compared with men. Conclusions . In a HFrEF outpatient cohort, the evaluation of plasma levels of both NPs and hsTnI can contribute significantly to identifying patients who have a worse prognosis, in addition to the echocardiographic assessment of right ventricular-arterial coupling.